2016
DOI: 10.1016/j.bbamem.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Global redesign of a native β-barrel scaffold

Abstract: One persistent challenge in membrane protein design is accomplishing extensive modifications of proteins without impairing their functionality. A truncation derivative of the ferric hydroxamate uptake component A (FhuA), which featured the deletion of the 160-residue cork domain and five large extracellular loops, produced the conversion of a non-conductive, monomeric, 22-stranded β-barrel protein into a large-conductance protein pore. Here, we show that this redesigned β-barrel protein tolerates an extensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 62 publications
1
33
0
Order By: Relevance
“…This is because in general membrane proteins have multiple tryptophan residues exposed to their hydrophobic interface. 24 We judge that it is not very convenient to use intrinsic tryptophan fluorescence for the FP-based spectroscopy studies for a number of reasons. They include complex contributions of individual-residue tryptophan spectra to the overall FP spectrum of the protein as well as rapid tryptophan quenching, because the indole nucleus is prone to electron donation during the excitation state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because in general membrane proteins have multiple tryptophan residues exposed to their hydrophobic interface. 24 We judge that it is not very convenient to use intrinsic tryptophan fluorescence for the FP-based spectroscopy studies for a number of reasons. They include complex contributions of individual-residue tryptophan spectra to the overall FP spectrum of the protein as well as rapid tryptophan quenching, because the indole nucleus is prone to electron donation during the excitation state.…”
Section: Discussionmentioning
confidence: 99%
“…2324 fhua Δc/Δ5l_t7 was created by inverse PCR using pPR-IBA1- fhua Δc/ Δ 5l-6×His + plasmid as a template. The PCR product was self-ligated to create pPR-IBA1- fhua Δc/ Δ 5l_t7-6×His +.…”
Section: Methodsmentioning
confidence: 99%
“…Neither did deletion of the plug give similar significant increase in high conductance channels, nor did pruning the loop do the same without pruning strand 8 [37]. Ultimately for FhuA, the more extreme the loop-pruning, the higher the conductance [38,39]. However, as would be expected, it has also been shown that in some proteins deletion of the plug does in fact lead to higher conductance.…”
Section: Outer Membrane Protein Designmentioning
confidence: 99%
“…Replacing positive residues with negative residues at the constriction site of P. denitrificans porin was also effective in creating cation selectivity [47]. A similar approach was also attempted by neutralizing the negatively charged residues on the loops of FhuA [39]. …”
Section: Outer Membrane Protein Designmentioning
confidence: 99%
“…We employed FhuA ΔC/Δ5L, an extensive truncation mutant (Fig. 1), 24 so that FhuA was converted from a non-ion conducting transmembrane protein 25 to a large-conductance nanopore. Therefore, this redesigned protein nanopore enabled parallel inspections of the anisotropy readout of detergent-refolded FhuA in solution and its ion transport activity, as judged by single-molecule electrophysiology in planar lipid membranes.…”
Section: Introductionmentioning
confidence: 99%